2021
DOI: 10.3390/biom11010097
|View full text |Cite
|
Sign up to set email alerts
|

Development of Possible Next Line of Systemic Therapies for Gemcitabine-Resistant Biliary Tract Cancers: A Perspective from Clinical Trials

Abstract: Biliary tract cancer (BTC) compromises a heterogenous group of tumors with poor prognoses. Curative surgery remains the first choice for localized disease; however, most BTC patients have had unresectable or metastatic disease. The gold standard therapy for these patients is chemotherapy with gemcitabine and cisplatin. There are no consensus guidelines for standard treatment in a second-line setting, although the data of the ABC-06 trial showed a slight survival benefit from oxaliplatin and 5-fluorouracil comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 144 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…Gemcitabine (GEM)-based chemotherapy is the standard of care for patients with advanced CCA [6][7][8], but primary or acquired resistance to GEM compromises therapeutic efficacy [9][10][11]. Potential targets that have been identified based on tumor genomic profiling, including FGFR2 fusion, IDH1 mutation, NTRK fusion, and BRAF mutation, provide therapeutic options after intolerance to or failure of GEM-based chemotherapy [12]. Previous studies have shown that the infiltration of immunosuppressive immune cells is associated with poor prognosis in CCA patients [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…Gemcitabine (GEM)-based chemotherapy is the standard of care for patients with advanced CCA [6][7][8], but primary or acquired resistance to GEM compromises therapeutic efficacy [9][10][11]. Potential targets that have been identified based on tumor genomic profiling, including FGFR2 fusion, IDH1 mutation, NTRK fusion, and BRAF mutation, provide therapeutic options after intolerance to or failure of GEM-based chemotherapy [12]. Previous studies have shown that the infiltration of immunosuppressive immune cells is associated with poor prognosis in CCA patients [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…Approximately 60% to 70% of advanced biliary tract cancer (ABTC) is diagnosed at an advanced stage with the historic 5-year survival rates of only 10% to 20% (2)(3)(4). Systemic therapy, including chemotherapy and targeted therapies based on genetic alternations, remains a standard treatment for ABTC (5).…”
Section: Introductionmentioning
confidence: 99%
“…( 4 ) In particular, two targeted agents, larotrectinib and pemigatinib, have been approved by the Food and Drug Administration for patients with cancers containing NTRK and FGFR2 fusion genes, respectively. ( 5 ) However, FGFR2 rearrangements occur in less than 20% of ICC cases, ( 6 ) and only 1 of 28 samples harbors the RABGAP1L‐NTRK1 gene fusion, ( 7 ) making FGFR2 and NTRK inhibitors clinically relevant only for a relatively small subset of patients. In addition, ivosidenib, a small‐molecule inhibitor of mutated IDH1, improved progression‐free survival of patients with ICC with IDH1 mutations; however, the IDH1 mutation was found in only approximately 13% of patients with ICC.…”
mentioning
confidence: 99%